Comparative Study for Photocatalytic Degradation of Bromo Phenol Blue by Some Nanoparticales Semiconductors - Amer Muosa Juda (Journal of Global Pharma Technology, 2018)
In this study, a comparison of different types of nanocatalyst such as zinc oxide nanoparticles, copper oxide nanoparticles and magnesium oxide nanoparticles on the photocatalytic activity efficiency of Bromo Phenol blue dye. Heterogeneous photocatalytic method was utilized; it was approved out by using UV (A) as light source. Some factors influence on the rate of the photocatalytic degradation of each catalyst were studied and compared and selected the most efficient nanocatalyst. The results of many factors, (such as weight of catalyst, primary dye concentration, pH of aqueous solution, and temperature) , shows that the photodecolorization and degradation is a pseudo-first order reaction giving to the Langmuir-Hinshelwood relationship. The experiments were carried out by varying weight of catalyst (0.02–0.07 g), initial concentration of dye (50–30ppm ) , pH solution  (1-11), and temperature range(298-313)K. The optimum conditions were approximated as: pH 3 when use ZnO NPs and pH = 5 when using both of CuO NPs and MgO NPs, catalyst amount of 0.06 g,0.05,  and 0.03g for ZnO NPs, CuO NPs and MgO NPs respectively. The degradation extents of 92.85%, 65.16% and 74.18% with ZnO NPs, CuO NPs and MgO, respectively obtained for BPB during 20 min irradiation and 30ppm dye concentration. The degradation extent was monitored by UV–vis spectroscopy. The Photocdecolorazation and degradation extent was observed increase with high temperature. Arrhenius plot shows that the Ea is equal to (29.7±1, and 18.54±1, 13.9±1) kJ mol-1 by using ZnO, CuO and MgO NPs respectively. The thermodynamic parameters of the photocatalytic degradation of BPB, like Ea, ΔH*, ΔS*and ΔG*showed the efficiency of the process. The most efficient nanocatalyst ZnO NPs>MgO NPs>CuO NPs